Dietary patterns and insomnia symptoms in Chinese adults: the China Kadoorie Biobank - Yu, C; Shi, Z; Lv, J; Guo, Y; Bian, Z; Du, H; Chen, Y; Tao, R; Huang, Y; Chen, J; Chen, Z; Li, L (MDPI, 2017)
Limited attention has been paid to the effect of dietary patterns on sleep problems. In the present study, we analyzed the cross-sectional data of 481,242 adults aged 30-79 years from the China Kadoorie Biobank. A laptop-based questionnaire was administered to collect information on food intakes and insomnia symptoms. Logistic regression was used to estimate the odds ratios of each insomnia symptom according to quartiles of each dietary pattern, with adjustment for potential confounders. Two major dietary patterns were derived by factor analysis. The traditional northern dietary pattern was characterized by high intakes of wheat and other staple food, whereas the modern dietary pattern was characterized by high intakes of meat, poultry, fish, eggs, fresh fruit, and dairy products. Both dietary patterns were associated with a decreased prevalence of insomnia symptoms (p for trend < 0.001); after adjustment for potential confounders, individuals who had the highest quartile score of traditional northern dietary pattern were 12%-19% less likely to have insomnia symptoms compared to those in the lowest quartile (odds ratio: 0.81-0.88), and the corresponding values for the modern dietary pattern were 0.89-1.01. Furthermore, interactions of these two dietary patterns on insomnia symptoms were observed. Further prospective studies are needed to elucidate the relationship between diet and insomnia.